Strategi Kepemimpinan Kepala Sekolah Dasar dalam Menangani Konflik antara Guru - Erwandi, Rudi; Marianita, Marianita; Prananosa, Ahmad Gawdy; Astuti, Linda (JOEAI (Journal of Education and Instruction), 2026)
The purpose of this study was to determine the leadership strategies elementary school principals use to handle conflicts among teachers. This study used a qualitative, phenomenological approach. The results showed that the principals' strategies for handling disputes between teachers included: gathering information from various sources, being objective, using deliberative, meditative, and counseling approaches, strengthening the team, prioritizing cooperation, and respecting mutual opinions. This resulted in the implementation of their primary duties and functions running smoothly and in the prevention of serious conflicts in the performance of their respective duties. In conclusion, the leadership strategies of elementary school principals in handling disputes between teachers included using deliberative, meditative, and counseling approaches, strengthening the team, prioritizing cooperation, and respecting mutual opinions.   Keywords: Conflict, Principal, Leadership, Strategy